Translation and cultural adaption of the Chronic Liver Disease Questionnaire for the Mandarin-speaking Chinese population in Singapore through cognitive debriefing. (March 2019) - Tan, Hiang Keat; Lee, Yean; Chia, Pei Yuh; Nurshifa, Shaik Hussain; Tan, Travis Kim Chye; Fook-Chong, Stephanie; Chang, Pik Eu; Fazila, Aloweni
Background: Patients with chronic liver disease often suffer from poor quality of life. The Chronic Liver Disease Questionnaire (CLDQ) is a validated tool to assess health-related quality of life in these patients. It has been translated and validated for use in many countries and languages globally. Objectives: We aimed to translate Mainland Chinese Mandarin to Singapore Mandarin and perform cross-cultural adaption of CLDQ for the Mandarin-speaking population in Singapore (CLDQ-SG). Methods: This study was conducted based on the International Society for Pharmacoeconomics and Outcomes Research Principles of Good Practice. The study consisted of two parts: part one involved cognitive debriefing and cultural adaption of CLDQ, and part two was a pilot study on the first version of CLDQ-SG among adult patients with chronic liver disease in a tertiary hospital. Results: During the cognitive debriefing process of part one, questions beginning with "recent" (最近) two weeks in Mandarin were changed to "last" (在过去) two weeks. Eighteen patients were recruited for part two of the study (50% male, mean age 49±13 years). Time taken to complete CLDQ-SG was 15±8 minutes, and the mean score was 5.1±0.5. The reliability of measurements for all domains was good, with an intra-class correlation coefficient ≥0.8. Items one and four needed further restructuring. There were no discrepancies between CLDQ and CLDQ-SG. Conclusion: This study showed that CLDQ-SG was culturally acceptable by the Mandarin-speaking population in Singapore. There were only two items that needed revision in the finalized CLDQ-SG.